2019
DOI: 10.1186/s13020-019-0243-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, pharmacology and analysis of Pseudostellaria heterophylla: a mini-review

Abstract: Pseudostellaria heterophylla is one of the well-known traditional Chinese medicines and has been used in clinics for 100 years in China. The chemistry and pharmacology of P. heterophylla were reviewed to understand its active compounds. Then analysis of these compounds related to quality control of this herb was discussed. For the analysis of chemicals, three aspects have been discussed in this review. The first two aspects focused on the methodologies for analysis of cyclic peptides and carbohydrates in P. he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Some drugs, like naldemedine and candidates from Super Natural II (SN00017653) and TCM (pseudostellarin C), have not been identified in previous studies as potential inhibitors of SARS-CoV-2 main protease and are suggested here for the first time. Interestingly, pseudostellarin C, which is a compound found in the roots of a traditional Chinese plant (Pseudostellaria heterophylla), is known medicinally for its application in dry cough arising from "lung dryness" (Hu et al, 2019). Naturally occurring compounds are a rich resource for drug innovation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs, like naldemedine and candidates from Super Natural II (SN00017653) and TCM (pseudostellarin C), have not been identified in previous studies as potential inhibitors of SARS-CoV-2 main protease and are suggested here for the first time. Interestingly, pseudostellarin C, which is a compound found in the roots of a traditional Chinese plant (Pseudostellaria heterophylla), is known medicinally for its application in dry cough arising from "lung dryness" (Hu et al, 2019). Naturally occurring compounds are a rich resource for drug innovation and development.…”
Section: Discussionmentioning
confidence: 99%
“…The activity might be due to the increased macrophage phagocytosis capacity and NK cell activity and the enhancements in T and Th cells, as well as IL-2, IL-6 and IL-12 secretion and IgA, IgG1 and IgG2b production. Pseudostellaria heterophylla (P. heterophylla) is often used for children as a substitute for ginseng because of its mild effects [33]. P. heterophylla polysaccharides have been proved to benefit chronic fatigue syndrome, and the underlying mechanisms of action involve neuroendocrine and immune systems [34].…”
Section: Biological Activities Of Biomacromolecules Based On Its Effimentioning
confidence: 99%
“…The substitution of Phe residue with Gly improves the water solubility of antamanide as well as the flexibility. The activity of antamanide derivatives was compared to that of pseudostellarin A ( PS-A ), a cyclic peptide isolated from Pseudostellaria heterophylla able to inhibit the tyrosinase activity [ 20 ]. A computational approach as molecular docking was used to understand at a molecular level the interactions occurring between the enzyme catalytic site and peptide inhibitors.…”
Section: Introductionmentioning
confidence: 99%